1998
DOI: 10.1007/s001340050627
|View full text |Cite
|
Sign up to set email alerts
|

Acute amiodarone-induced lung toxicity

Abstract: Acute amiodarone pulmonary toxicity is a definite pathological entity in ICU patients. High oxygen concentrations may be a risk factor, while pre-existing pathology, e. g. ARDS, may mask its development. Amiodarone should be used with caution in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 7 publications
0
30
0
1
Order By: Relevance
“…We aim to place the spinal 1 to 2 interspaces caudal to the epidural so that the theoretical risk of puncture of the catheter by the spinal needle is avoided. It has been suggested that the incidence of bacterial meningitis following CSE in labour might be related to the proximity of the skin, a foreign body (catheter) and a dural puncture hole [7]. With a separate needle technique a one or two interspace gap can be left between spinal insertion and epidural insertion sites.…”
Section: Pencil-point Needles and Combined Spinal Epidural Block Whymentioning
confidence: 99%
See 1 more Smart Citation
“…We aim to place the spinal 1 to 2 interspaces caudal to the epidural so that the theoretical risk of puncture of the catheter by the spinal needle is avoided. It has been suggested that the incidence of bacterial meningitis following CSE in labour might be related to the proximity of the skin, a foreign body (catheter) and a dural puncture hole [7]. With a separate needle technique a one or two interspace gap can be left between spinal insertion and epidural insertion sites.…”
Section: Pencil-point Needles and Combined Spinal Epidural Block Whymentioning
confidence: 99%
“…Amiodarone treatment carries significant risk: a recent study showed a relationship between the pathological features of amiodarone-induced pulmonary toxicity and the acute use of amiodarone for supraventricular tachycardias in patients with acute respiratory distress syndrome [7]. Caution in its use in this patient group has been recommended.…”
Section: Magnesium and Atrial Fibrillationmentioning
confidence: 99%
“…131 bpm (4) 103 bpm (20) 132 bpm (26) 0.14 (11) (20) 136 bpm (29) 1.42 (13) 0.8 (11) (31) 0.37 (31) 0.26 (46) Residual variability, bpm 16 (2) Abbreviations: AT = Atrial fibrillation; Amio 50 = Amiodarone dosage that induces 50% of putative maximal effect on HR reduction; DOBU = beta-agonist administration; bpm = beats per minute; BSV = between-subject variability; ECV : electrical cardio-version; FILL = fluid therapy; FRetro HR = factor determining the importance of endogenous spontaneous retrocontrol of the HR to a reference HR depending on the type of cardiac rhythm at the time of first administration of amiodarone in ICU; HR 0 = heart rate at t 0 before first amiodarone dosing in ICU; ICU = intensive care unit; KDE = rate constant describing the equilibrium between the administration rate and the observed effect, k out = first-order constant rate for Amio effect kinetics; %rse = percent relative standard error; NA = not applicable; MG = magnesium loading; Parox = Paroxystic atrial tachyarrhythmia which started less than one FIGURE 1…”
Section: Amiodarone Doses Receivedmentioning
confidence: 99%
“…However, it can be associated with hypotension and potentially severe liver and pulmonary toxicity, particularly after IV administration [4,[13][14][15] . This toxic risk justifies the administration of the lowest possible dose to control heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…However, typical pathological patterns were recently found in almost half of the patients treated with amiodarone prior to death from ARDS [4]. Moreover, pulmonary toxicity was also reported in patients receiving low-dose amiodarone over prolonged periods [5].…”
Section: Introductionmentioning
confidence: 99%